Therapeutically harnessing extracellular vesicles - Cheng, Lesley; Hill, Andrew F (Nature reviews. Drug discovery, 2022)
The field of extracellular vesicle (EV) research has developed rapidly over the last decade from the study of fundamental biology to a subject of significant clinical relevance. The potential of harnessing EVs in the diagnosis and treatment of diseases - including cancer and neurological and cardiovascular disorders - is now being recognized. Accordingly, the applications of EVs as therapeutic targets, biomarkers, novel drug delivery agents and standalone therapeutics are being actively explored. This Review provides a brief overview of the characteristics and physiological functions of the various classes of EV, focusing on their association with disease and emerging strategies for their therapeutic exploitation.